Hemolysis associated toxicities of benthic dinoflagellates from Hong Kong waters. (June 2020) - Yan, Meng; Leung, Priscilla T.Y.; Gu, Jiarui; Lam, Veronica T.T.; Murray, J. Sam; Harwood, D. Tim; Wai, Tak-Cheung; Lam, Paul K.S.
Abstract: Benthic dinoflagellates produce a diverse range of phycotoxins, which are responsible for intoxication events in marine fauna. This study assessed the hemolysis associated toxicities of six species of benthic dinoflagellates from the genera Coolia, Fukuyoa, Amphidinium and Prorocentrum . Results demonstrated that Amphidinium carterae, Coolia tropicalis and Fukuyoa ruetzleri were the three most toxic species, while Prorocentrum cf. lima did not have significant hemolytic effect. Grouper samples ( Cephalopholis boenak ) were more tolerant to the hemolytic algae than the blackhead seabream ( Acanthopagrus schlegelii ), with decreased heart rate and blood flow being observed in medaka larvae after exposure to toxic algal extracts. LC-MS/MS analysis detected a gambierone analogue called 44-methylgambierone produced by the C. tropicalis isolate. This analogue was also detected in the F. ruetzleri isolate. This study provided new information on the hemolysis associated toxicities of local toxic benthic dinoflagellates, which contributes to better understanding of their emerging threats to marine fauna and reef systems in Hong Kong. Highlights: Rapid screening of hemolysis associated toxicity of benthic dinoflagellates in marine fish. Species of Coolia, Fukuyoa and Amphidinium could induce hemolysis in marine fish. Cephalopholis boenak was more tolerant to toxic algae than Acanthopagrus schlegelii . Hemolytic algae can cause lethality, decreasing heart rate and blood flow in marine medaka. 44-Methylgambierone was detected in Coolia tropicalis and Fukuyoa ruetzleri .